2020
DOI: 10.3892/mmr.2020.11649
|View full text |Cite
|
Sign up to set email alerts
|

Laminin‑332 mediates proliferation, apoptosis, invasion, migration and epithelial‑to‑mesenchymal transition in pancreatic ductal adenocarcinoma

Abstract: The poor prognosis of patients with pancreatic ductal adenocarcinoma (PDAC) is primarily due to the invasive and metastatic behaviors of this disease. Laminin-332 (LM-332) is a key component of the basement membrane barrier, and is associated with tumor metastasis. The present study provides evidence towards the potential function of LM-332 in carcinoma, indicating the distinct roles of the three LM-332 subunits (α3, β3 and γ2) in cell proliferation, migration, invasion, apoptosis and the epithelial-to-mesench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Particularly, laminin proteins appear to be ubiquitously distributed within the stroma, creating a discontinuous basement membrane [77]. Among the laminin, laminin 5 (consisting of subunits α3, β3, and γ2) has been shown to mediate proliferation, apoptosis, invasion, migration and epithelialto-mesenchymal transition in vitro [78,79] and it is negatively associated with patients' survival [80]. It interacts with cells through focal adhesion and hemidesmosomes formed via the interaction with α3β1 integrin and α6β4 integrin.…”
Section: Fibrosis and Ecm Remodeling Affect Pancreatic Microenvironmentmentioning
confidence: 99%
“…Particularly, laminin proteins appear to be ubiquitously distributed within the stroma, creating a discontinuous basement membrane [77]. Among the laminin, laminin 5 (consisting of subunits α3, β3, and γ2) has been shown to mediate proliferation, apoptosis, invasion, migration and epithelialto-mesenchymal transition in vitro [78,79] and it is negatively associated with patients' survival [80]. It interacts with cells through focal adhesion and hemidesmosomes formed via the interaction with α3β1 integrin and α6β4 integrin.…”
Section: Fibrosis and Ecm Remodeling Affect Pancreatic Microenvironmentmentioning
confidence: 99%
“…Previously, we reported that extracellular Ser restriction decreased total glutathione content and led to the generation of H 2 O 2 and induction of inflammation-related gene expression in mouse embryonic fibroblasts deficient in Phgdh [ 5 ]. Recent studies also demonstrated that Phgdh deletion elicited an inflammation-like response through the production of cytokines via an increase in reactive oxygen species in chondrocytes [ 41 ], while orally administered Ser was able to protect LPS-induced intestinal inflammation via p53-mediated glutathione synthesis [ 42 ]. Hence, it is presumed that a decrease in the glutathione content and/or a dysregulation of the mitochondrial electron transport system lead to oxidative stress in the liver of LKO mice, which may trigger inflammation-like responses in the liver of LKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the kinase resulted in lower laminin expression. Furthermore, recent studies on pancreatic ductal adenocarcinoma cells revealed that knockdown of individual LAM genes resulted in different cell activity (proliferation/migration/EMT) ( 13 ). It is known that soluble factors, such as TGF-β, EGF and PGGF play a role ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…LN-332 has the highest affinity for α6β4 integrin, which stabilizes the binding of cells to the basement membrane through hemidesmosomes ( 12 ). Moreover, LN-332 promotes cell polarization, proliferation, and apoptosis ( 13 ). A soluble form of LN-332 causes activation of protein kinase C (PKC), phosphatidyl inositol 3-kinase (PI3K), and mitogen-activated protein kinase (MEK) signaling pathways ( 14 ).…”
Section: Introductionmentioning
confidence: 99%